PERSEBARAN FLORA DAN FAUNA ENDEMIK PAPUA BARAT: STUDI PADA CENDRAWASIH, KUSKUS, ANGGREK EPIFIT, DAN MATOA BERDASARKAN IUCN - Nurmala Berutu; Yosella Manullang; Ludista Masindi; Yudha Rumapea; Farouq Ghazali Matondang; Mulhady Putra (STKIP Subang, 2025)
This study examines the distribution patterns and ecological characteristics of four endemic species of West Papua—birds-of-paradise, cuscus, epiphytic orchids, and matoa—based on secondary data from the IUCN Red List and other biodiversity resources. Using a descriptive qualitative approach, the research synthesizes scientific literature, conservation reports, and spatial information to describe how biogeographical factors in the Australasian region shape endemism in Papua Barat. Data on habitat type, elevation ranges, ecological preferences, and conservation status were analyzed to identify distribution tendencies across major ecological zones such as lowland forests, montane areas, wetlands, mangrove ecosystems, and karst landscapes. The results highlight that each species occupies distinct ecological niches, with variations influenced by forest structure, microclimate, and environmental conditions. The study also identifies major threats—including habitat modification, land-use change, hunting pressure, and ecosystem degradation—which continue to affect population stability and habitat availability. Overall, this research provides an updated synthesis of ecological and distributional information to support conservation understanding of West Papua’s endemic flora and fauna, emphasizing the importance of monitoring and management in regions undergoing rapid landscape transformation.